Entrepreneurship and vocational education : identifying the classroom practice of vocational education teachers towards integrating selected areas of entrepreneurship education perceived as important by entrepreneurs - 565319 Widad Othman (Sekudai : UTM, 1995)
The purpose of this study was to identify the classroom practices of vaocational education teachers towards integrating selected areas of entrepreneurship eduation perceived as important by entrepreneurs. In order to investigatae this problem, eleven specific questions were developed. This selection of teachers throughout Peninsular Malaysia were according to a prpoportionate cluster sampling technique. Systmematic random sampling procedure were used for the selection of entrepreneurs within Kuala Lumpur and its outskirts. Due to the nature of the problem, two sets of questionaires, with similar contents but different format were developed. The questionnaires were administered by personal visits or mailed. The data collected were analyzed using both descriptive and inferential statistics. The eta correlation coefficient wasused to determine the relationships between variables, with the F ststistics t-test and the Oneway Analysis of Variance were used to measure to the difference among variables. A .05 level of significance was chosen in reporting the data. Vocational teachers and entrepreneurs beleived entrepreneurship education should be taught at the upper secondary level; either offered as an elective course or integrated buvocational teaachers into their courses. Both groups of respondents perceived self-confident and diligence as the most important entrepreneurial characteristics. Entrepreneurs beleived entrepreneurial knowledge and skills are very important for operating any business. These knowledge and skills are being substantantially integrated by vocational teachers into their courses; but not according to their importance as identified by entrepreneurs. Furthermore, the teachers classroom pracatices were influenced by their area of teaching, interest and experience in business. Vocational teachers were interested to integrate entrepreneurship education into their courses because it will create awareness among students. No traininng ini entrepreneurship was the main reason cited by teachers not interested in integrating entrepreneurship eduation into their classroom.